Soil Health Card A tool for better productivity - Saha, Bholanath; Basak, Nirmalendu; Saha, Sushanta; Singh, Pancham Kumar; Hazra, G C; Mandal, Biswapati (Indian Farming, 2016)
Soil health card makes the farmers aware of the nutritional status of the soil. Future cropping patterns can be planned judiciously by the farmers using soil health cards leading to increased productivity. The soil health cards are being issued to the farmers based on the soil test database. The recommendations are also recorded in the soil health cards.